2022
DOI: 10.3390/healthcare10010134
|View full text |Cite
|
Sign up to set email alerts
|

Burnout, Depression and Sense of Coherence in Nurses during the Pandemic Crisis

Abstract: During the COVID-19 pandemic, the risk to nurses’ mental health has increased rapidly. The aim of the study was to investigate the prevalence of depression and burnout and to evaluate their possible association with the sense of coherence in nursing staff during the pandemic crisis. The Copenhagen Burnout Inventory questionnaire, Beck’s Depression Inventory, and the Sense of Coherence questionnaire were completed by 101 male and 559 female nurses. Individual and demographic data were recorded. Regarding depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 46 publications
(54 reference statements)
3
21
0
Order By: Relevance
“…to relieve work pressure. In terms of professional identity, it is possible to help young nurses integrate into the collective through further education, learning, group activities, etc., to strengthen team awareness and professional identity, to enable nurses to find the meaning and value of their work [ 53 , 54 ]. Institutional and leadership arts can reduce nurses' invisible absenteeism by improving nurses' psychological coherence through incentives and inclusive leadership [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…to relieve work pressure. In terms of professional identity, it is possible to help young nurses integrate into the collective through further education, learning, group activities, etc., to strengthen team awareness and professional identity, to enable nurses to find the meaning and value of their work [ 53 , 54 ]. Institutional and leadership arts can reduce nurses' invisible absenteeism by improving nurses' psychological coherence through incentives and inclusive leadership [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted among nurses by Pachi et al also highlighted that burnout is a factor influencing depression. In this study, regression evidenced that 43.7% of the variation in the BDI (Beck’s Depression Inventory) rating was explained by the CBI (Copenhagen Burnout Inventory) [ 17 ]. Kaschka et al also indicated that burnout is likely to be a risk factor for developing depression [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors believed that, despite the fact that a strong correlation coefficient was obtained between these variables, the interpretation of the variation of depression from burnout at the level of 43.7% cannot justify the overlap between burnout and depression. The authors adopted the position of the World Health Organization, which treats burnout as a separate disease [ 17 ]. We also adopted this concept in our study.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, students in the nursing field experienced more traumatic events during the COVID-19 pandemic crisis than before it [ 62 ]. The sense of coherence may act as a negative regulator between burnout and depression and it has been reported to be reduced by the influence of the COVID-19 pandemic [ 63 ]. Our study was developed before the COVID-19 pandemic crisis; thus, it is possible that during the COVID-19 crisis and also the post COVID-19 crisis, other specific life events could show a relationship with burnout.…”
Section: Discussionmentioning
confidence: 99%